Where is Yuyu?: detective theme Augmented Reality (AR) children’s book - Ahmad Sazali, Nur Izzah Sakina; Norihsan, Nurfatin Aqilah; Rodzuan, Aida Nadhirah; Mustafa, A’dillah (Universiti Teknologi Mara, Kedah, 2022)
Where is Yuyu? is a detective theme Augmented Reality (AR) children’s book that combines physical books and mobile applications. AR can enhance teaching and learning methods, especially in children. Recently AR technology has evolved in children’s exploration and introductory books, and less has been embedded in the storyline books, which explain the whole story. “Where is Yuyu?” is intended to cultivate children to the hybrid reading method allowing children to interact with the books using three dimensions characters using the Artivive application. The existence of “Where is Yuyu” will spark reading motivation among children as they enjoy the benefit of reading and venturing into technology. This innovation aims to enhance children’s creativity through advanced visual activities in a book, introduce books and technology in a fun way for children, and give parents ways to introduce daily chores to their children. “Where is Yuyu? is Malaysia’s first detective theme augmented reality children’s book. This book is significant in increasing motivation and boosting reading interest among children, improving concentration, memory, imagination, and problem-solving skills among children, helping children to understand concepts faster and better, and providing an alternative for children with disabilities to understand concepts and the environment faster.